2002
DOI: 10.1128/jvi.76.22.11254-11264.2002
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nonstructural Protein nsP2 and Alpha/Beta Interferons in Determining the Outcome of Sindbis Virus Infection

Abstract: Alphaviruses are a group of significant human and animal pathogens. The nearly 30 members of this genus are transmitted by mosquitoes to higher vertebrates that serve as amplifying hosts (54). Alphaviruses cause different diseases but have similar replication strategies and life cycles. In insect vectors, they cause persistent lifelong infections and viral replication does not critically affect the viability of the hosts (51). These viruses also often establish persistent infection in cultured mosquito cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
270
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(282 citation statements)
references
References 66 publications
12
270
0
Order By: Relevance
“…HEK293T cells were transfected using XtremeGENE 9 DNA Transfection Reagent (Roche) whereas HeLa cells and MEFs were transfected using Lipofectamine 2000 (Invitrogen). Sindbis virus encoding the enhanced green fluorescent protein (EGFP) from a duplicated subgenomic promoter (TE/5′2J/GFP) has been previously reported (46). Stocks were prepared and titers determined on BHK-J cells with 10-fold serial dilutions of sample, and then plaques were visually enumerated after crystal violet staining, as previously described (25); multiplicities of infection (MOI) were calculated based on BHK-J-derived titers.…”
Section: Methodsmentioning
confidence: 99%
“…HEK293T cells were transfected using XtremeGENE 9 DNA Transfection Reagent (Roche) whereas HeLa cells and MEFs were transfected using Lipofectamine 2000 (Invitrogen). Sindbis virus encoding the enhanced green fluorescent protein (EGFP) from a duplicated subgenomic promoter (TE/5′2J/GFP) has been previously reported (46). Stocks were prepared and titers determined on BHK-J cells with 10-fold serial dilutions of sample, and then plaques were visually enumerated after crystal violet staining, as previously described (25); multiplicities of infection (MOI) were calculated based on BHK-J-derived titers.…”
Section: Methodsmentioning
confidence: 99%
“…13,14) In Sindbis virus-host cell interactions, a viral nonstructural protein, nsP2, which is a component of the replicative enzyme complex required for replication and transcription of viral RNAs, plays a role in suppressing the antiviral response in Sindbis virus-infected cells. 15) In this study, we report the identification, purification, and characterization of a 26.5-kDa gut-juice protein showing antiviral activities. The expression of this protein in larvae from seven multivoltine and six bivoltine strains of B. mori was also evaluated to draw y To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…It has been reported that this shut-off affects many proteins involved in the IFN response, a mechanism developed by alphaviruses to escape antiviral innate responses. 38 This virus-induced type I IFN response can synergize with other cytokines or tumor antigens expressed from the SFV vector, resulting in good antitumor responses. 27,28,41 However, we have shown that overexpression of IFNa from SFV in the absence of other therapeutic transgenes is non-redundant and, moreover, essential to achieve a therapeutic antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…37 In addition, BHK cells can support the replication of noncytopathic alphavirus RNA mutant replicons, in contrast to cell lines with an intact type I IFN response where those replicons are rapidly lost. [38][39][40] Not only is the production of SFV-IFN feasible but IFNa expression could also be achieved in infected cells independently of endogenous type I responses. We have observed that on infection with SFV-IFN, similar levels of IFNa are expressed in TC-1 and L929 cells, in spite of the fact that TC-1, the main tumor target cells used in our study did not seem to develop a type I IFN response after infection with SFV-LacZ control virus (Figure 1f).…”
Section: Discussionmentioning
confidence: 99%